The analysis of data of the long-term follow-up study in patients with schizophrenia with the first episode at youthful age - S. A. Golubev (Кубанский научный медицинский вестник, 2015)
In this review opinions of various researchers on a problem of a course of the schizophrenia with the first episode at youthful age are described. Lack of identical views on character of a long course of schizophrenia, frequent contradictions in opinions of certain scientists and psychiatric schools as a whole attracts attention. It is noted on that fact that timely diagnostics and correctly picked up complex therapy can correct disease manifestations in many respects. Need of carrying out complex research with attraction of a number of neurobiological, clinical genetic, neurophysiological, neuropsychological, clinical psychological and psychopathological techniques which will allow to receive the most objective ideas of character of a course of schizophrenia and its outcomes locates in the review.